The Politics of Belonging in India : Becoming Adivasi. - Rycroft, Daniel J. (Taylor & Francis, 2011)
Since the 1990s, the Indigenous movement worldwide has become increasingly relevant to research in India, re-shaping the terms of engagement with Adivasi (Indigenous/tribal) peoples and their pasts. This book responds to the growing need for an inter-disciplinary re-assessment of Tribal studies in postcolonial India and defines a new agenda for Adivasi studies. It considers the existing conceptual and historical parameters of Tribal studies, as a means of addressing new approaches to histories of de-colonization and patterns of identity-formation that have become visible since national indepen.